India-Pakistan Dispute on Kashmir: Pakistan's Allegiance in the Effortsof "War on Terrorism" of the United States after the WTC 9/11 Attack - Napang, Marthen; Nurhasanah, Siti; Rohman, Syaiful (Journal of Terrorism Studies, 2019)
When the Cold War took place, the Soviet Union took side on India. Consequently, the US made Pakistan as its ally. Then after the Cold War was over and allegedly Pakistan helped the Afghan terrorist forces, US turned to side with India. But it turns out it was only Indian trickery to get support from the US. After the 9/11 WTC attack, the US set priorities that fighting against terrorism was more important. The US sided to Pakistan and invited Pakistan to work together to fight against Afghan terrorists. In this discussion paper, the author will explore and analyze what kind of win-win cooperation that the US and Pakistan have. The author applies theory of neo-realism, concept of power, and concept of national interest to analyze the case.